Modeling the phase evolution in alkali-activated slag cements upon interaction with seawater - Kamasani Chiranjeevi Reddy; G.M. Kim; Solmoi Park (Case Studies in Construction Materials, 2022)
The stability of different phases in a binder exposed to seawater is essential when assessing the performance of structures in a marine environment. The understanding of stability of alkali-activated slag upon interaction with seawater is insufficient. In this study, phase changes in alkali-activated slag systems upon interaction with seawater were investigated by employing thermodynamic calculations. The results show that C-N-A-S-H and Mg-Al LDH, the main reaction product phases in alkali-activated slag systems, are stable at lower seawater quantities and destabilize to ettringite and M-S-H with an increase in the seawater content. M-S-H, Al(OH)3 and calcite are observed to be the stable phases within the interaction mass of seawater considered here. The Ca/Si ratio of C-N-A-S-H reached a value of ∼1 at a higher seawater content regardless of the activator used. A significant increase in the volume of the system is observed during the destabilization of C-N-A-S-H. The current study improves our understanding of the spurious volume changes of different phases in alkali-activated slag systems upon interaction with seawater.